NO SHEEP SACRIFICED IN KAMPUNG NAGA STUDY ON CELEBRATIONS THE EID AL-ADHA AND THE HAJAT SASIH IN KAMPUNG NAGA, TASIKMALAYA - Bambang Misno (Al-Albab, 2013)
People will do their best to apply their religious beliefs in the form of different religious rituals as a means of reconciling themselves to God. Among the rituals is Idhul Adha festivity held by the indigenous people of Kampung Naga. This festival is very interesting as it continues with the ritual of Hajat Sasih as a form of grateful expression to the ancestors of the community of Kampung Naga. The results of this research showed that the practice of Eid al-Adha Celebration was held with great solemnity according to the Islamic teachings, although there are no sheep sacrificed. The attitude of respect for the custom over Idhul Adha celebration has made them prefer the customary ritual in the form of Hajat Sasih to Idhul Adha which is a sunnah. The Hajat Sasih Ritual is carried out after the completion of the Idhul Adha prayer. The ritual is performed in accordance with the procedures carried out by their ancestors by delivering the Pahajat (parcel containing food and produce) to the Punduh and the Lebe a day before the celebration. Meanwhile, the Punduh and the Lebe also gave their pahajat to the Kuwu (village chief) and the Naib (caretaker)of Neglasari Village. The Hajat Sasih is an expression of gratitude to God represented in the form of a visit to the tomb of the ancestor, i.e. Sembah Dalem Eyang Singaparana . In addition, the Hajat Sasih also serves as a special occasion for the people of Kampung Naga to visit each other and expect the blessing from the visit to the grave and from the rice cone that has been prayed upon by the elders of the village. Keywords: Local Islam, Eid al-Adha, Hajat Sasih, Kampung Naga and visiting the grave.